CURRICULUM TYPOLOGY OF ISLAMIC RELIGION EDUCATION IN INTEGRATED ISLAMIC SCHOOL (SIT) - Sofanudin, Aji (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractIn the last ten fifteen years, the Integrated Islamic School (SIT) has grown rapidly. At first this school grew in urban areas, but now it has penetrated into the periphery. One of them is thriving in Tegal Regency. This study aims to determine the typology of the Islamic Education curriculum at the SMP IT in Tegal Regency. This research is a qualitative study with direct observation of three schools. The research findings indicate that the typology of Islamic education curriculum at the SMP IT in Tegal Regency are various. At least there are three variants of SIT, i.e. (1) SIT under the cope of Network of Integrated Islamic School (JSIT) as practiced by SMP IT Luqman Al-Hakim, (2) SITÂ which follow the course of aswaja as practiced by SMP IT Al-Azhar, and (3) SIT which is Islamic Nationalist, as in SMP IT Bimantara Al-Furqon. Those three viariants of SIT have differences in implementing the education curriculum of Islamic religion. SIT JSIT applies the combination curriculum of education department and JSIT curriculum. SIT Aswaja applies the education authorities curriculum and Islamic boarding school, while Nasionalist SIT applies the combination of education authorities curriculum and the foundationâ€™s curriculum.Abstrak Sepuluh lima belas tahun terakhir ini berkembang pesat sekolah-sekolah yang menggunakan label Sekolah Islam Terpadu (SIT). Pada awalnya sekolah ini tumbuh di daerah perkotaan, tetapi sekarang sudah merambah ke wilayah pinggiran. Salah satunya adalah tumbuh subur di Kabupaten Tegal. Penelitian ini bertujuan untuk mengetahui tipologi kurikulum Pendidikan Agama Islam pada SMP IT di Kabupaten Tegal. Penelitian ini merupakan penelitian kualitatif dengan observasi secara langsung ke tiga sekolah. Temuan penelitian menunjukkan bahwa tipologi kurikulum pendidikan agama Islam pada SMP IT di Kabupaten Tegal beragam. Setidaknya terdapat tiga varian SIT, yakni (1) SIT di bawah naungan Jaringan Sekolah Islam Terpadu (JSIT) sebagaimana dipraktekkan oleh SMP IT Luqman Al-Hakim, (2) SIT yang berhaluan aswaja sebagaimana dilaksanakan oleh SMP IT Al-Azhar, dan (3) SIT yang bersifat nasionalis Islam, sebagaimana terdapat pada SMP IT Bimantara Al-Furqon. Ketiga varian SIT tersebut memiliki perbedaan dalam implementasi kurikulum pendidikan agama Islam. SIT JSIT menerapkan kurikulum kombinasi dinas pendidikan dan kurikulum JSIT, SIT Aswaja menerapkan kurikulum dinas pendidikan dan pesantren, serta SIT Nasionalis menerapkan kombinasi kurikulum dinas pendidikan dan kurikulum yayasan.